Elusive Development in the Balkans: Research Findings - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2016)
Research findings of the latest round of the wiiw-GDN project on development in the Balkans are surveyed. Historical and structural deficiencies of development in the Balkan countries are discussed in detail with emphasis of the role of investment, integration, and structural and policy deficiencies. These structural features have led to policy challenges in particular after the crisis of 2008-2009. Which are investment- and export-led growth, which implies slower growth of consumption than national savings; slow growth of wages and incomes over the period of structural adjustment and for reasons of prevention of real exchange rate appreciation; and free access to foreign markets due to slower recovery of domestic demand. With the policy framework biased towards rigidity, and having in mind the needed structural adjustment, development policies that are compatible with them are infrastructure, physical and institutional, investments supported by the EU and regionally; trade integration – regional, European, and within the World Trade Organisation; financial and entrepreneurial cooperation within the manufacturing networks in the EU primarily; sustainable macroeconomic policies especially when it comes to external balances. A list of studies and of the relevant literature is included.
Keywords: N14; N74; O14; O18; O20; P27; R11; R41; 330; development; Balkans; infrastructure; crisis; integration; state failure; investment; consumption